Timing of Closure of a Protective Loop-Ileostomy Can Be Crucial for Restoration of a Functional Digestion - Werner, Jens M.; Kupke, Paul; Ertl, Matthias; Opitz, Sabine; Schlitt, Hans J.; Hornung, Matthias (Frontiers in Surgery, 2022)
Introduction. Protective loop-ileostomy is one of the most common interventions in abdominal surgery to provide an alternative intestinal outlet until sufficient healing of a distal anastomosis has occurred. However, closure of a loop-ileostomy is also associated with complications. Thus, knowledge of the optimal time interval between primary and secondary surgery is crucial. Methods. Data from 409 patients were retrospectively analysed regarding complications and risk factors for closure-associated morbidity and mortality. A modified Clavien-Dindo classification of surgical complications was used to evaluate the severity of complications. Results. A total of 96 (23,5%) patients suffered from postoperative complications after closure of the loop-ileostomy. Early closure within 150 days from enterostomy (n=229) was associated with less complications (p<0.001**). Looking at the severity of complications, there were significantly more (p=0.014*) mild postoperative complications in the late closure group (>150 days). Dysfunctional digestive problems - either (sub-) ileus (p=0.004*), diarrhea or stool incontinence (p=0.003*) - were the most frequent complications associated with late closure. Finally, we could validate in a multivariate analysis that ‘time to closure’ (p=0.002*) is independently associated with the development of complications after closure of a protective loop-ileostomy. Conclusion. Late closure (>150 days) of a loop-ileostomy is an independent risk factor for post-closure complications in a multivariate analysis. Nevertheless, circumstances of disease and therapy need to be considered when scheduling the closure procedure.